Income and Well-Being in Latin America - Rojas, Mariano (Springer, 2024)
In general terms the Latin American region is a middle-income one. On average, it is not a region where starvation and economic calamities prevail, but in some countries large segments of the population may be in difficult economic situation. The income situation usually attracts the attention of policy makers because a close and strong relations between income and well-being is assumed; however, this chapter shows that the relationship between income and well-being is neither simple nor straightforward; it also shows that economic growth is not necessarily associated to greater well-being.
Keywords: income; well-being; Latin America; WOS(2)